2020
DOI: 10.1108/par-09-2019-0118
|View full text |Cite
|
Sign up to set email alerts
|

Geographical diversification and corporate liquidity in Malaysia: a quantile regression approach

Abstract: Purpose This paper aims to examine the effect of geographical diversification on corporate liquidity in Malaysian firms. Liquidity is represented by both cash and working capital. Design/methodology/approach Data for this study is collected from a total of 735 firms over a period of five years, from 2010 to 2014, resulting in a total of 2,904 firm-year observations. The effect of geographical diversification on the cash and working capital of the firms is analyzed by using the ordinary least squares (OLS) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Christina and Ekawati (2014) and Luo and Hachiya (2005) found that institutional ownership negatively affected the company's cash holding. Corporate liquidity policy is proxied by cash holding, current ratio, liquid ratio, absolute liquid ratio, cash conversion cycle, and working capital (Bagchi & Chakrabarti, 2014;Bokpin et al, 2011;Wasiuzzaman, 2019).…”
Section: Corporate Governance and Liquidity Policymentioning
confidence: 99%
“…Christina and Ekawati (2014) and Luo and Hachiya (2005) found that institutional ownership negatively affected the company's cash holding. Corporate liquidity policy is proxied by cash holding, current ratio, liquid ratio, absolute liquid ratio, cash conversion cycle, and working capital (Bagchi & Chakrabarti, 2014;Bokpin et al, 2011;Wasiuzzaman, 2019).…”
Section: Corporate Governance and Liquidity Policymentioning
confidence: 99%
“…Furthermore, emerging markets are imperfect and dispose of a high level of information asymmetry causing a high cost of external funds and creating a preference for internal funds (Wasiuzzaman, 2020). Third, nowadays there is a great awareness about exploring and examining the role of CG mechanisms in Islamic countries because they have different characteristics such as culture, beliefs and laws.…”
Section: Introductionmentioning
confidence: 99%
“…For both small and large firms, GD influences profitability only for firms with low and high levels of profitability, respectively. A recent study also used the QR technique to investigate the impact of GD on corporate liquidity (Wasiuzzaman, 2020). It was discovered that the GD has a significant influence on firm cash holdings only for firms with low‐cash holdings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As a result, the impact of diversification on firm performance in advanced economies context may vary. Finally, it is discovered that Malaysian firms have had stable reported performance over a long period of time (Gyan, 2017; Lee & Hooy, 2018; Wasiuzzaman, 2020). As a result, using Malaysian firms as a sample, the effect of diversification on performance can be quantified in considerable detail.…”
Section: Introductionmentioning
confidence: 99%